2022
DOI: 10.1155/2022/4299280
|View full text |Cite|
|
Sign up to set email alerts
|

Application of the Improved Clustering Algorithm in Operating Room Nursing Recommendation under the Background of Medical Big Data

Abstract: The nursing work in the operating room has the characteristics of long time, strong technicality, and heavy work, which have an important influence on the quality of the operation. Operating room nursing recommendations based on data mining technology can solve a series of practical problems in clinical nursing and nursing management. This paper selects the clustering algorithm in commonly used data mining technology as the research object and actually analyzes the impact of this algorithm in operating room nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Second, better survey results and lower HAMA and HAMD scores were determined in group A versus group C, which we think is due to the application effect of cluster nursing. Through cluster nursing, the professionalism and dynamics of nursing services can be guaranteed, reflecting the pertinence and integrity of nursing measures [ 32 , 33 ]. Among them, the psychological attention to patients can enable them to fully understand the treatment methods and related operations, as well as self-regulation of bad emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, better survey results and lower HAMA and HAMD scores were determined in group A versus group C, which we think is due to the application effect of cluster nursing. Through cluster nursing, the professionalism and dynamics of nursing services can be guaranteed, reflecting the pertinence and integrity of nursing measures [ 32 , 33 ]. Among them, the psychological attention to patients can enable them to fully understand the treatment methods and related operations, as well as self-regulation of bad emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Corey Heerschap et al in the study (Algorithmic approaches to ostomy management: An integrative review) concluded Current literature demonstrates the potential benefit of ostomy management algorithms to standardize and improve ostomy patient care ( 22 ). Xiaofang Wu et al in the study “Application of the Improved Clustering Algorithm in Operating Room Nursing Recommendation under the Background of Medical Big Data,” concluded data mining technology based on the improved clustering algorithm could effectively improve the quality of care during the nursing period in the operating room, obviously can stabilize the various indicators of the patient during the operation, greatly improve the negative emotions of the patient, and increase the satisfaction of nursing work ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical nursing and nursing administration face a number of real problems that can be resolved with the aid of data mining-based operating room nursing recommendations. The broadly used data mining method of clustering is selected as the study's object of research by Wu et al [17], and the effect of this algorithm on operating room nursing suggestions is examined. In China, there is currently very little data mining technology development in the nursing profession.…”
Section: Related Workmentioning
confidence: 99%